2014
DOI: 10.1089/end.2014.0215
|View full text |Cite
|
Sign up to set email alerts
|

Predicting an Effective Ureteral Access Sheath Insertion: A Bicenter Prospective Study

Abstract: Insertion of a 14F UAS before RIRS may fail in approximately one-fifth of the patients. An indwelling Double-J stent, a history of previous ureteroscopy or Double-J stent, and older age are all significant predictors for an effective 14F UAS insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 22 publications
3
73
2
1
Order By: Relevance
“…In these cases, the placement of a JJ stent was mandatory and resulted in a successful UAS placement two weeks after stent placement. These results are comparable to other studies in where the failure Non-available 0 0 2 (1.5 %) 19 (7.5 %) 9 (6.7 %) 13 (9.7 %) rate of insertion for the 14Fr UAS is up to 22 % despite progressive dilatation [10]. There were two UAS malfunctions (1.5 %) in which the procedure could be finalized by usage of a conventional UAS.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In these cases, the placement of a JJ stent was mandatory and resulted in a successful UAS placement two weeks after stent placement. These results are comparable to other studies in where the failure Non-available 0 0 2 (1.5 %) 19 (7.5 %) 9 (6.7 %) 13 (9.7 %) rate of insertion for the 14Fr UAS is up to 22 % despite progressive dilatation [10]. There were two UAS malfunctions (1.5 %) in which the procedure could be finalized by usage of a conventional UAS.…”
Section: Discussionsupporting
confidence: 81%
“…This concept was evaluated prospectively in a multicentric setting. Although the Flexor©Parallel™ UAS is available in different sizes (9.5-14 Fr internal size) for this study, the 12/14 Fr was used as it is considered the standard UAS and permits the entry of all flexible ureteroscopes in particular the digital ureteroscope which needs an internal 12Fr caliber and is the most employed in the five centers [7,10]. Our successful placement rate was 94 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This auxiliary instrument is commonly preferred in RIRS cases up to 86% and used to facilitate the reentry into the ureter, decrease operative time and improve SFRs, particularly, in the treatment of large renal stones [24]. However, UAS cannot be placed into the ureter and may fail in one-fifth of the patients [25]. A prospective study investigated the ureteral wall injuries resulting from the insertion of a 14F UAS in 359 patients and revealed an 86.6% rate of low-grade injuries [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, UAS usage may be a double-edged sword: on the one hand diminishing risks related to irrigation and on the other hand increasing risks related to access in a narrow ureter [5]. However, the access related injuries might be related to not only the limited size of the ureter, but also the dynamics of the organ [4, 6]. We have previously shown that the β -agonist isoproterenol (ISO), when administered locally in a 0.1  μ g/mL saline solution at an irrigation rate of 8 mL/min, was able to inhibit the ureteral muscle tone and lower the pressure in the upper urinary tract significantly during ureterorenoscopy without causing systemic adverse effects [710].…”
Section: Introductionmentioning
confidence: 99%